MHD mixed convection in copper-water nanofluid filled lid-driven square cavity containing multiple adiabatic obstacles with discrete heating - Gorla, Rama Subba Reddy; Siddiqa, Sadia; Hasan, Alfaisal A.; Salaheldin, Taher A.; Rashad, Ahmed M. (Zielona Góra: Uniwersytet Zielonogórski)
The objective of the present work is to investigate the influence of nanoparticles of copper within the base fluid (water) on magneto-hydrodynamic mixed-convection flow in a square cavity with internal generation. A control finite volume method and SIMPLER algorithm are used in the numerical calculations. The geometry is a lid-driven square cavity with four interior square adiabatic obstacles.
Keywords: nanofluid; mixed convection; magneto-hydrodynamics; square cavity; adiabatic obstacles